KETERAMPILAN BAHASA INGGRIS BAGI MAHASISWA JURUSAN PERHOTELAN: "LINK AND MATCH" DUNIA PENDIDIKAN DAN DUNIA KERJA (Jurnal Pariwisata Bunda, 2022)
This article aims at highlighting what English skills are demanded by hotel employees. The findings are necessary to link and match what English skills demanded in workplaces and what to be prepared by vocational institutions. The data were gained through shared questionnaires written in google form. 14 hotel general managers (GM) and Human Relationship Developments (HRD) in the Province of West Sumatera, Indonesia responded. The findings proved that the most English skill needed in the hotel industry was speaking skill followed by listening skill. Most hotel recruitments used English as one of the tests. The most international standard test used was TOEFL-Like Test. Other tests used were conversation tests and interviews in English. These findings suggest that vocational institutions should be keenly concerned with improving students’ ability in English skills.